Islam and Muslim women in Southeast Asia: past, present, and future - Hashim, Rosnani (2012)
Islam made its presence in the Malay-Riau archipelago, which comprised the bulk of Southeast Asia today, very early in its history. The Islam that was embraced blended quite well and peacefully with the local cultures and traditions. Historically, the success of its women was evident from the fact that Acheh had queens ruling the Muslim kingdom for a certain period. Presently, this success is also evident in the leadership and management roles occupied by Muslim women in almost all fields in Malaysia. This paper examines the advancement of Muslim women in selected countries in the region, how they negotiated for various spaces in their lives, the factors enhancing and impeding their progress and their present status. It also attempts to look at the social changes and challenges brought about by the new realities – Muslim women who are well-educated, having a career outside of the home, active in social and political works, or financially independent -- and also the future of Islam and Muslim women in the region.